Students’ Perceptions toward the Use of Grammarly in Checking Grammar in Assignments - Mirza Ananda; Rahmatun Nisa; Siti Safura (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2021)
This study aimed to find out about the students’ perceptions of the use of Grammarly in checking grammar in written assignments and the students’ obstacles when using Grammarly. This quantitative study used questionnaire to collect the data. The participants of the study were ten students from semester sixth of the English Department at a private university in Banda Aceh, Indonesia. The results of the study showed that many students gave positive responses toward using Grammarly to learn and check their grammar in assignments. In addition, the study found that the students’ obstacles when using Grammarly included some issues such as problems in the internet connection and lack of understanding of Grammarly suggestions. The study suggests that Grammarly to be applied for grammar checking among EFL students.